Chromosomal similarities between Nephilidae and Tetragnathidae indicate unique evolutionary traits among Araneoidea - Araujo, D.; Paula-Neto, E. [UNESP]; Brescovit, A. D.; Cella, D. M.; Schneider, M. C. (Taylor & Francis, 2015)
Nephilid systematics has been subject to several changes in the last years, and the use of non-classical characters could be useful for evolutionary considerations. In this study, we analyzed the mitotic chromosomes of two nephilid spiders, Nephila clavipes and Nephila sexpunctata, using standard staining, silver nitrate impregnation and C-banding techniques, aiming to discuss the chromosomal similarities of Nephilidae and Tetragnathidae, and chromosome evolution within Nephila and Nephilingis. The basic karyotype characteristics observed in these two species (2n♂ = 22 + X1X20 and monoarmed chromosomes) were similar to those registered for most araneoid families, i.e., Araneidae, Linyphiidae, Nephilidae, Nesticidae and Tetragnathidae. However, the occurrence of both prominent secondary constrictions and nucleolar organizer regions (NORs) is a shared characteristic between Nephilidae and Tetragnathidae, considering that these regions were not observed in any other Araneoidea species cytogenetically examined. Furthermore, in the present study we showed that within Nephila and Nephilingis species, change in the number and location of NORs as well as in the quantity and distribution of constitutive heterochromatin were the main events responsible for chromosome evolution, and that these differences can be useful in the cytotaxonomy of this group.
Keywords: Chromosomes; karyotype evolution; nucleolar organizer region; Orbiculariae; secondary constriction